'Northmen, Southmen, comrades all'? The adoption of discourse like by migrants north and south of the Irish border. (November 2020) - Corrigan, Karen P.; Diskin, Chloé
Abstract: The Republic of Ireland (ROI) and Northern Ireland (NI) have recently become attractive migrant destinations. Two main dialectal varieties are recognised on the island, but little is known about their adoption by new speakers. Focusing on a panlectal feature, discourse like, we conducted a quantitative sociolinguistic investigation of its adoption by seventeen young Polish and Lithuanian migrants in Armagh (NI), and thirty-six Polish and Chinese adult migrants in Dublin (ROI), with comparator samples drawn from native speakers. Findings show that like rates in both cities diverge, but that migrants mirror local frequencies. Clause-final like is restricted primarily to native speakers, but is twice as frequent in Armagh than in Dublin. English proficiency has a significant effect on the likelihood of young migrants in Armagh adopting the clause-final variant. The article's significance also stems from the original contribution it makes to our understanding of how sociolinguistic competence is acquired in 'superdiverse' settings. (Discourse like, identity, migration, Northern Irish-English, Hiberno-English, Ulster English, Southern Irish-English)*